2004
DOI: 10.1007/s00213-004-1883-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased responsiveness of presumed 5-HT cells to citalopram in adult rats subjected to prolonged maternal separation relative to brief separation

Abstract: These findings suggest that early life stress gives rise to persistent changes in the function, but not the density or mRNA expression of central 5-HT(1A) receptors and/or 5-HT transporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 48 publications
(53 reference statements)
6
44
1
3
Order By: Relevance
“…Previous reports suggested that neonatal maternal separation may decrease 5-HTergic activity of the raphe nucleus at adulthood (Gartside et al, 2003;Arborelius et al, 2004). In this study, we demonstrated that mRNA expression of serotonin reuptake transporter (5-HTT) in the raphe nucleus of adult rat is decreased by experience of neonatal maternal separation.…”
Section: Decreased 5-htt Expression In the Raphe Nucleusmentioning
confidence: 50%
See 1 more Smart Citation
“…Previous reports suggested that neonatal maternal separation may decrease 5-HTergic activity of the raphe nucleus at adulthood (Gartside et al, 2003;Arborelius et al, 2004). In this study, we demonstrated that mRNA expression of serotonin reuptake transporter (5-HTT) in the raphe nucleus of adult rat is decreased by experience of neonatal maternal separation.…”
Section: Decreased 5-htt Expression In the Raphe Nucleusmentioning
confidence: 50%
“…5-HT neurotransmission in the hippocampus is believed to be involved in the regulation of HPA axis activity throughout life. Indeed, it has been reported that periodic maternal separations during pre-weaning period result in persistent alterations in 5-HT concentrations (Matthews et al, 2001) and www.elsevier.com/locate/neures Neuroscience Research 58 (2007) [32][33][34][35][36][37][38][39] 5-HTergic functions in selective brain regions including the hippocampus (Gartside et al, 2003;Arborelius et al, 2004;Van Riel et al, 2004). Furthermore, stress response of adrenocorticotrophic hormone (ACTH) was blunted concomitantly with increased 5-HT turnover in the hippocampus in rats with neonatal maternal separation (Daniels et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth pointing out, therefore, that stress exposure likely impacts this mechanism via changes in 5-HT1A-R expression and function in the hippocampus. An increase in hippocampal 5-HT1A-R binding or mRNA is seen in rodents exposed to glucocorticoids, unpredictable stress, amygdalakindling, and, in some studies at least, maternal separation (Arborelius et al, 2004;Harvey et al, 2003;Kalynchuk et al, 2006;Lopez et al, 1999;Neumaier et al, 2002;Vazquez et al, 2000Vazquez et al, , 2002.…”
Section: Role Of 5-ht1a Receptorsmentioning
confidence: 98%
“…However, despite one study reporting no gross alteration in SERT-mediated reuptake in the rat forebrain under acute stress (Martin et al, 2000), and evidence of decreased DRN SERT mRNA in chronically socially stressed rats (McKittrick et al, 2000) (cf. Arborelius et al, 2004;Vazquez et al, 2000) it is not fully clear how SERT function is altered by stress. Notwithstanding, alterations in SERT-mediated reuptake would be predicted to be an important mechanism by which the serotonin system can self-regulate the amount of synaptic serotonin evoked by stress.…”
Section: Serotonin Reuptakementioning
confidence: 99%
See 1 more Smart Citation